Perancangan Sistem Akuntansi Persediaan Pakan Ikan Berbasis Google Spreadsheet pada Usaha Budidaya Perikanan - Andreuw Kristian Pantow; Sintia Nurani Korompis; Hedy Desiree Rumambi; Raymond Festus Rombot; Yelly Paendong (Prodi Akuntansi FE Universitas Maritim Raja Ali Haji, 2024)
This study aims to design a fish feed inventory record at UD Bless using Google Spreadsheets. The research method is qualitative. Primary data in this study were obtained by conducting direct interviews with business owners. Secondary data in this study are in the form of transaction evidence, inventory records arranged in archives. The results of the study are the design of a feed inventory accounting system at UD Bless which consists of a list of feed inventory, inventory purchases and sales, cash and credit inventory purchases, cash and credit inventory sales, and profitability of each type of inventory.